ANTIFUNGAL POTENTIAL OF EXTRACTS AND FRACTIONS OF Randia nitida LEAVES ON SOYBEAN PATHOGENS AND THEIR PHYTOCHEMISTRY - STHEFANY CAROLINE BEZERRA DA CRUZ-SILVA (Revista Caatinga, 2016)
This study aimed to evaluate the antifungal activity of methanol extract and fractions of leaves of Randia nitida (Kunth) DC on Colletotrichum truncatum (Schw.) Andrus & Moore, Rhizoctonia solani Kühn and Sclerotinia sclerotiorum (Lib.) De Bary and perform chemical and antioxidant activity tests. Crude methanol extract (EBM) and fractions (hexane = FHX, dichloromethane = FDM and ethyl acetate = FAE) underwent classical phytochemical analysis and determination of total phenols, flavonoids and antioxidant activity. Samples were individually incorporated into PDA culture mediums (potato-dextrose-agar) at concentrations of 10, 20, 40, 80 and 160 μg mL - 1 of extract or fraction. Mycelial growth was evaluated when control reached the edge of the plate. Phytochemical results indicated that flavonoids, steroids and triterpenoids are the major chemical constituents in both EBM and fractions. Total phenols, flavonoids and antioxidant activity were higher for FAE and EBM, followed by FDM and FHX; however, the latter showed higher content of steroids and triterpenoids compared to the other fractions. For C. truncatum , R. solani and S. sclerotiorum , the most efficient fractions were respectively FAE, FDM and FHX, all of them in the highest concentration (160 μg mL - 1 ). The highest inhibition rate was observed against S. sclerotiorum , reaching 93.75%. We concluded that all fractions have antifungal activity on the plant pathogens, being FHX the most active against S. sclerotiorum , which might have been due to the presence of steroids and triterpenes.